2018
DOI: 10.1016/j.scitotenv.2018.05.116
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate change and climate anomalies on hydrologic and biogeochemical processes in an agricultural catchment of the Chesapeake Bay watershed, USA

Abstract: Nutrient export from agricultural landscapes is a water quality concern and the cause of mitigation activities worldwide. Climate change impacts hydrology and nutrient cycling by changing soil moisture, stoichiometric nutrient ratios, and soil temperature, potentially complicating mitigation measures. This research quantifies the impact of climate change and climate anomalies on hydrology, nutrient cycling, and greenhouse gas emissions in an agricultural catchment of the Chesapeake Bay watershed. We force a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 62 publications
3
40
0
1
Order By: Relevance
“…; Wagena, Collick, Ross, Rau, et al. ). SWAT‐VSA uses the same land use data as does SWAT, but the soil layer is a spatial combination of the Food and Agriculture Organization‐United Nations Educational, Scientific and Cultural Organization Digital Soil Map of the World (FAO ) and topographically derived wetness classes derived from the TI generated across the watershed (D.R.…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations
“…; Wagena, Collick, Ross, Rau, et al. ). SWAT‐VSA uses the same land use data as does SWAT, but the soil layer is a spatial combination of the Food and Agriculture Organization‐United Nations Educational, Scientific and Cultural Organization Digital Soil Map of the World (FAO ) and topographically derived wetness classes derived from the TI generated across the watershed (D.R.…”
Section: Methodsmentioning
confidence: 98%
“…; Wagena, Collick, Ross, Rau, et al. ; Wagena and Easton ). Climate change models downscaled to the regional level generate predictions of precipitation and temperature under historical and future climate scenarios in order to drive the SWAT‐VSA model.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…On Maryland's Lower Eastern Shore, companion SWAT modeling studies by Renkenberger et al (2016; 2017) in a 298‐km 2 agricultural basin indicated a two‐ to threefold expansion of critical source areas of P loss with climate change that led to an 80% increase in P export relative to current conditions. Elsewhere, a SWAT–VSA modeling study by Wagena et al (2018) in a sloping 7.3‐km 2 agricultural basin in east‐central Pennsylvania suggested annual total P export could increase by up to 11%, with the majority of the load increase driven by higher wintertime stream flows. Taken together, these studies found that more efficient and additional best management practices above and beyond those currently planned would be needed to maintain the P loading targets specified by the Chesapeake Bay TMDL in a changing climate.…”
Section: Climate Changementioning
confidence: 99%